Chemically clean synthesis and characterization of graphene oxide‐poly(acrylic acid–sodium styrene sulfonate) composite thermostable elastic gel encapsulating copper nanoparticles for efficient catalytic reduction of 4‐nitrophenol. Issue 18 (18th January 2018) - Paul Guin, Jhimli; Bhardwaj, Y. K.; Varshney, Lalit
ABSTRACT: The thermostable chemically blended elastic poly‐(acrylic acid–sodium‐styrene‐sulfonate–graphene oxide) super‐absorbent hydrogel was synthesized by additive‐free gamma‐radiation induced polymerization followed by crosslinking method. It showed the best swelling ratio in water due to its porous nature. The composite material adsorbed 98 mg/g Cu(II) at room temperature from the aqueous solution of Cu(II) at pH 5 by the chemi‐adsorption of Cu(II) ions at several energetically heterogeneous functional groups. The copper nanoparticles (CuNPs) of size 12 ± 8 nm had been synthesized in situ by chemical reduction of the pre‐adsorbed Cu(II) ions. The functional groups of composite hydrogel served as complexing agent and nano‐reaction sites. Avoiding any pre‐reduction induction time, the inexpensive CuNPs catalytically completely decolorized the aqueous solution of 4‐nitrophenol (4‐NP) within 60 s in the presence of NaBH4 at a promising calculated rate constant (9.0 × 10 −2 /s) ever reported in the literatures. It is in contrast to the commonly noticeable phenomenon for other CuNPs‐based catalysis of 4‐NP. The composite hydrogel matrix helped to retain the catalytic activity of CuNPs and simultaneously it helped in the osmotic inclusion of 4‐NP into the reaction cites. This composite hydrogel synthesized through a chemically clean method could be utilized for efficient conversion of hazardous chemical 4‐NP to industrially important chemical 4‐aminophenol. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46200. Abstract :